Polyphenol supplementation benefits human health via gut microbiota: A systematic review via meta-analysis. (March 2020) - Ma, Guiling; Chen, Yanting
Graphical abstract: Highlights: Study human gut microbiota abundance affected by polyphenol intake via meta-analysis. Polyphenol supplementation increased health promoting microbiota abundance of Lactobacillus, Bifidobacterium, and decreased the abundance of Clostridium pathogenic species. Polyphenol supplementation had dose-dependent effect on gut microbiota abundance, and the suggested supplementation dose was less than 540 mg/d. Abstract: Polyphenol supplementation attracts much research attentions due to beneficial effects on human health. Gut microbiota significantly shape human health, but polyphenols in changing human gut microbiota remain elusive. This study aimed to use meta-analytic methods to reveal the effects of polyphenol-rich foods on the abundance of human gut microbiota. Significant heterogeneity analysis showed the polyphenol intake dose and sources variedly affected on abundance of gut microbiota. Polyphenol supplementation stimulated the abundance of Lactobacillus and Bifidobacterium health promoting species, but inhibited the abundance of Clostridium pathogenic species in gut microbiota of human subjects. Notably, peak increase of abundance of Lactobacillus, Bifidobacterium, and Clostridum health promoting species was at polyphenol intake of 396 mg/d, 540 mg/d, and 593 mg/d respectively. Taken together, polyphenol supplementation shapes gut microbiota species, contributing to benefits in human health.